(untitled) (Huellas, 2015)
The present work aims at analyzing the housing and urban legislation policies developed at different state levels, and their materialization in the urban space of Tandil (provinceofBuenos Aires,Argentina). In the last decades, a worsening of conflicts related to housing deficit in some neighborhoods was observed in the city ofTandil, fact which contrasts sharply with the power of real estate activities such as the construction of residences for high-income sectors and tourism-related uses located in other zones of the urban area. This work seeks to explore, on the one hand, which action has been taken by the State to guarantee access to housing for the underprivileged social sectors. For this purpose, data supplied by the Ministry of Social Development from the Municipality of Tandil will be used. On the other hand, by using documentary techniques, this work seeks to know the urban planning policies implemented by the provincial and municipal governments, looking into the restrictions imposed on real estate speculation in the most dynamic sectors of the urban area, that have a strong impact on the sales and rental prices of housing in the rest of the town.